The Effectiveness of Big Book Media Stimulation and Hand Puppets In The Language Development of Children Aged 3-4 Years - Annisa Bayu Heriani; Munayarokh Munayarokh; Siti Chunaeni (Poltekkes Kemenkes Semarang, 2023)
Background: Children's brain development reaches 50% by the age of four, 30% until the age of eight, 20% until adulthood. Compared to other developments, language is the main key for children to be used as a means of communication. To optimize it, media in the form of big books and hand puppets are needed to stimulate children's language. This study aims to determine the effectiveness of big book and hand puppet media stimulation in the language development of children aged 3-4 years.. Methods: The cluster sampling method was used to determine the number of children to be studied based on a population of 80 children in the playgroup, while proportionate random sampling was used for the distribution of children to be stimulated with big book media and hand puppets based on a sample of 46 children. Results: The results of the Mann-Whitney Test obtained a p-value in each media, namely 0.00 with a mean value of 17.65 in big book media and a mean value of 8.13 in hand puppet media. Conclusion: The use of big book media has proven to be more effective in stimulating language development and being able to captivate children's attention and know the story in the big book which has advantages in terms of size, text, and large big book images compared to other story books.